Catolicismo popular: práticas e apropriações em Quirinópolis de 1943 a 1997 - Andrade, Wesley Lima de (2012)
This study sought to address the religious field the town of Quirinópolis, State of Goiás, in the period between the years1943 to 1997, from a cultural bias, leading to an understanding of culture quirinopolina from popular religious practices. Based on the concepts of popular culture, memory and representation, we seek to understand the changes occurring within the religious aspects quirinopolino specifically on issues that include thepopular manifestations of these aspects. Within movements andexisting representations in religion as a cultural expression, isseeking a review of existing representations of power from theseevents, leading to identification of a \"popular priests\" against the \"official priests.\" To get these issues addressed, the workconsisted of analysis of interviews, as well as documents relatingto the time studied.